Dilemma of Distance Learning Policies in the Cultural Framework of Early Marriage in Ambunten-Sumenep, East Java - Hanik, Umi; Tannisyafolia, Ratih Himamatul Azizah; Ningtyas, Trimurti (Didaktika Religia, 2022)
This study analyses the influence of distance learning policies implemented in Indonesia during the pandemic period (2019-2021) on instances of early marriage in the Ambunten District of Sumenep Regency, East Java. This study utilises primary data obtained from interviews with children who were married early between December 2019 and April 2021. Five informants who had been married at an early age were selected for interview. Furthermore, observations were conducted regarding the implementation of distance learning and early marriage in the region. The findings indicate that distance learning plays a role in perpetuating the culture of early marriage in Sumenep District. This is perceived as a means of mitigating the impact of young people's association, namely adultery. The absence of parental guidance and support, coupled with the lack of environmental and structural support for early marriage, results in students prioritising marriage over education.